2000
DOI: 10.1007/s001250051346
|View full text |Cite
|
Sign up to set email alerts
|

Effects of gestational diabetes on human placental glucose uptake, transfer, and utilisation

Abstract: Both pregestational [1] and gestational diabetes mellitus [2,3] can lead to neonatal macrosomia which is associated with fetal death, prematurity, birth trauma, and neonatal respiratory distress syndrome, hypoglycaemia, polycythaemia, hyperbilirubinaemia, hypocalcaemia, hypomagnesaemia and cardiomyopathy [4±6]. For macrosomic neonates, birth weight has not been consistently shown to positively correlate with the degree of control of maternal blood glucose [7,8], suggesting that factors other than or in additio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
48
0
5

Year Published

2000
2000
2017
2017

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 74 publications
(55 citation statements)
references
References 36 publications
2
48
0
5
Order By: Relevance
“…Our results add further weight to our previous observation that glucose handling by the placenta alters in women who are pregnant and have GDM compared with women who have a normal pregnancy [7]. In ad- dition, this study suggests that glucose handling by placentae from GDM pregnancies is different depending on whether the women received insulin therapy or not.…”
Section: Discussionsupporting
confidence: 77%
See 3 more Smart Citations
“…Our results add further weight to our previous observation that glucose handling by the placenta alters in women who are pregnant and have GDM compared with women who have a normal pregnancy [7]. In ad- dition, this study suggests that glucose handling by placentae from GDM pregnancies is different depending on whether the women received insulin therapy or not.…”
Section: Discussionsupporting
confidence: 77%
“…Another study used a similar approach to investigate glucose handling by in vitro perfused placentas [7]. The latter study found significant reductions in mean net glucose transfer and direct materno-fetal transfer in a GDM-Diet group compared with the non-diabetic control group.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The ubiquitously expressed GLUT-1 isoform is inversely related to extracellular glucose concentration in placenta (17) whereas GLUT-4, which is found to a lesser extent in the placenta, are insulin sensitive GLUTs (18). Studies have demonstrated diminished glucose uptake in placental tissue from individuals with GDM (19)(20)(21)(22) and furthermore, increased expression of GLUT-1 in placenta basal membranes from GDM women in comparison with normal controls (23,24).…”
Section: Introductionmentioning
confidence: 99%